Chromatic Discrimination in a Cortically Colour Blind Observer. - Heywood, C; Cowey, A; Newcombe, F (1991)
We tested the ability of a subject with cerebral achromatopsia to discriminate between colours and to detect chromatic borders. He was unable to identify colours or to arrange them in an orderly series or choose the odd colour out of an array or even to pick out a colour embedded in an array of greys. Nevertheless, he could select the odd colour when the colours were contiguous, even when they were isoluminant, and could discriminate an ordered from a disordered chromatic series as long as the colours in each row abutted one other. His verbal replies showed that he did so by detecting an edge between two stimuli that were, to him, perceptually identical. Introducing a narrow isoluminant grey stripe between adjacent colours abolished or greatly impaired this ability. As long as isoluminant colours were contiguous the patient could identify the orientation of the chromatic borders. Photopic spectral sensitivity showed evidence both for activity of three cone channels and for chromatic opponent processing, indicating that postreceptoral chromatic processing is occurring despite the absence of any conscious awareness of colour. The results indicate that both parvocellular colour opponent and magnocellular broad-band channels are active and that the cortical brain damage has selectively disrupted the appreciation of colour but not the ability to detect even isoluminant chromatic borders, which would be invisible to a retinal achromat. The subject's performance on non-colour tasks involving the discrimination of shape, texture, greyness and position was excellent. His disorder is therefore not like that of macaque monkeys in which cortical area V4 has been removed, and which are much more severely impaired at discriminating shape than colour.